York platelet syndrome is a CRAC channelopathy due to gain-of-function mutations in STIM1 - Markello, Thomas (Mol Genet Metab, 2014)
Store-operated Ca(2+) entry is the major route of replenishment of intracellular Ca(2+) in animal cells in response to depletion of Ca(2+) stores in the endoplasmic reticulum. It is primarily mediated by the Ca(2+) selective release-activated Ca(2+) (CRAC) channel which consists of the pore-forming subunits ORAI1–3 and the Ca(2+) sensors, STIM1 and STIM2. Recessive loss-of-function mutations in STIM1 or ORAI1 result in immune deficiency and nonprogressive myopathy. Heterozygous gain-of-function mutations in STIM1 cause non-syndromic myopathies as well as syndromic forms of miosis and myopathy with tubular aggregates and Stormorken syndrome; some of these syndromic forms are associated with thrombocytopenia. Increased concentration of Ca(2+) as a result of store-operated Ca(2+) entry is essential for platelet activation. York Platelet syndrome (YPS) is characterized by thrombocytopenia, striking ultrastructural platelet abnormalities including giant electron opaque organelles and massive, multi-layered target bodies and deficiency of platelet Ca(2+) storage in delta granules. We present clinical and molecular findings in 7 YPS patients from 4 families, demonstrating that YPS patients have a chronic myopathy associated with rimmed vacuoles and heterozygous gain-of-function STIM1 mutations. These findings expand the phenotypic spectrum of STIM1-related human disorders and define the molecular basis of YPS.